EKSPLORASI PENGALAMAN SISWA DALAM PEMBELAJARAN IPA MALALUI PBL BERBASIS AR UNTUK MENDORONG BERPIKIR KRITIS - Yulianti Wibowo; Rinto; Zakiyyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Creative thinking skills are one of the most important competencies in facing the challenges of the 21st century. However, the reality on the ground shows that many students still struggle to develop new ideas, lack the courage to express their ideas, and are unable to solve problems innovatively. This is due to conventional learning approaches and the lack of use of interactive media. This study aims to describe the effectiveness of applying the Problem-Based Learning (PBL) model based on Augmented Reality (AR) media in enhancing students' creative thinking skills. The method used is descriptive qualitative, with data collection techniques including observation, in-depth interviews with teachers, and the dokumentation. The research subjects were seventh-grade students at SMP Negeri 3 Kota Cirebon. Data analysis was conducted using a thematic approach to identify patterns in the learning process and outcomes. The results of the study indicate that the implementation of the AR-based PBL model can create an active and enjoyable learning environment, increase student participation, and encourage the emergence of creative ideas. Students appeared more enthusiastic, were more willing to express their opinions, and were able to solve problems collaboratively. Teachers also stated that the use of AR helps clarify the material and stimulates students' curiosity. Thus, the AR-based PBL model has proven effective in enhancing creative thinking skills and can be an innovative solution in science education.